The cognitive overlap between linguistic, social and human sciences in the field of applied linguistics - BOUCETTA, Mahmoud; MOUHOUBI, Samira (Journal of Human Sciences, 2025)
This article deals with cognitive overlap and applied linguistics between linguistic, social and human sciences, and the choice of these sciences was due to their importance in human life and society, and this study aims to reveal the prominent role in the issue of overlap between linguistic, social and human sciences, and to know their advantages, problems and rules and the role of this integration in establishing social and psychological linguistics. Finally, access to the importance of interdisciplinary sciences in solving linguistic problems related to psychology and sociology. In addition to the importance of integration between science, and the integration of knowledge with reality, to establish the most important branches of applied linguistics.